Sustainability Appraisal: Quantitative Methods and Mathematical Techniques for Environmental Performance Evaluation - Erechtchoukova, Marina G.; Khaiter, Peter A.; Golinska, Paulina; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
One of the most important issues in developing sustainable management strategies and incorporating ecodesigns in production, manufacturing and operations management is the assessment of the sustainability of business operations and organizations$1 (Boverall environmental performance. The book presents the results of recent studies on sustainability assessment. It provides a solid reference for researchers in academia and industrial practitioners on the state-of-the-art in sustainability appraisal including the development and application of sustainability indices, quantitative methods, models and frameworks for the evaluation of current and future welfare outcomes, recommendations on data collection and processing for the evaluation of organizations$1 (Benvironmental performance, and eco-efficiency approaches leading to business process re-engineering.s
Sustainability indicators: development and application -- Formal methods for organization$1 (Bs environmental performance evaluation -- Sustainable resource management -- Environmental monitoring for sustainability assessment -- Quantitative methods and models for environmental assessment -- Eco-efficiency and business opportunities for sustainable performance -- Environmental-economic accounting.s
Keywords: Environmental sciences; Biotechnology; Sustainable development; Environmental economics; Environment; Environmental Engineering/Biotechnology.; Sustainable Development; Environmental Economics